What do patients value in the hospital meal experience?. (1st January 2016) - Hartwell, Heather J.; Shepherd, Paula A.; Edwards, John S.A.; Johns, Nick
Abstract: A number of previous studies have reported on the aspects of hospital food service that patients value, but usually as a secondary finding, and not generally based upon patient-centred approaches. This study employed a questionnaire produced ab initio from interviews with patients and hospital staff, the data from which were subjected to factor and cluster analysis, in order to identify and prioritise the factors that contribute to the meal experience empirically. The most important factors, food and service were as identified by other authors. In decreasing order of importance were social, personal and situational factors. The results confirm that improving the quality of the food and the efficiency with which it reaches the patients remain the most important objectives of hospital food service. Highlights: Another look at the factors that make up patients' meal experience in hospital. Questionnaire: developed from observations and interviews of hospital patients and staff. Analysis: factorisation and clustering to identify external and internal factors. Regression to prioritise. Findings: decreasing order of priority: food, service, social, personal and situational factors. Conclusion: food and efficient service should receive the greatest attention in hospital food provision.